Jigs and fixtures design for separation and printing process in a pen manufacturing company - 195191 Muhamad Mustakim Musa (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2003